2001
DOI: 10.1097/00129492-200109000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dysfunctional Eustachian Tube by Video Endoscopy

Abstract: Slow-motion endoscopic video analysis is a potentially useful technique in classifying types of pathologic changes in the eustachian tube. Additional studies of dysfunctional tubes are needed to predict outcomes in operative ear cases and to design intratubal therapy for chronically dysfunctional tubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
135
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(145 citation statements)
references
References 7 publications
4
135
0
5
Order By: Relevance
“…Active and passive exchange of middle ear gases occurs constantly within the middle ear [20]. Poe, et al [21] reported that normal ETs had four consistent sequential movements: [1] palatal elevation causing passive, then active, rotation of the medial cartilaginous lamina; [2] lateral excursion of the lateral pharyngeal wall; [3] dilation of the lumen, caused primarily by tensor veli palatini muscle movement beginning distally and inferiorly, then opening proximally and superiorly; and [4] opening of the tubal valve at the isthmus caused by dilator tubae muscle contraction [21]. In the present study, sevoflurane is eliminated quickly, and CO 2 diffused into the middle ear cavity is removed quickly due to the function of the ET and also increased microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Active and passive exchange of middle ear gases occurs constantly within the middle ear [20]. Poe, et al [21] reported that normal ETs had four consistent sequential movements: [1] palatal elevation causing passive, then active, rotation of the medial cartilaginous lamina; [2] lateral excursion of the lateral pharyngeal wall; [3] dilation of the lumen, caused primarily by tensor veli palatini muscle movement beginning distally and inferiorly, then opening proximally and superiorly; and [4] opening of the tubal valve at the isthmus caused by dilator tubae muscle contraction [21]. In the present study, sevoflurane is eliminated quickly, and CO 2 diffused into the middle ear cavity is removed quickly due to the function of the ET and also increased microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Edema of ET mucosa could affect tubal motion either from bulk effect, mechanical thickening, and stiffening of the walls or from secretory proteins with increased fluid viscosity. This could be secondary to primary mucosal disease, inflammatory conditions, infection, or allergy and could result in functional closure of the ET lumen [9].…”
Section: Discussionmentioning
confidence: 99%
“…Video endoscopy of Eustachian tube is a promising, efficient and effective newer modality as it gives us, direct real time visualization of the ET and direct assessment of ET functioning [4].…”
Section: Introductionmentioning
confidence: 99%
“…role of mucosal disease and muscular abnormalities in reducing the mechanical ability of the tube to dilate. As specific disease processes are identified, the possibility of future medical or surgical treatments may become easier and more of a reality [13].…”
Section: Discussionmentioning
confidence: 99%